Binational, Multidisciplinary and Evolutionary: Arctic's Tradition and the Future of the Arctic Institute - Robinson, Michael P. (ARCTIC, 1987)
In its 40 years of continuous quarterly publication, the journal Arctic has traced the intellectual history of Canadian and American northern science as driven by concerns for a variety for northern topics, including political systems, natural resources, military activities, cultural change, sovereignty assertion and natural science. Clearly, the future of northern scholarship deeply involves integrated polar information systems and some kind of centrally recognized polar institute entraining binationalism, a multidisciplinary approach and systematic circumpolar publication. Self-governing, self-reliant and land-owning tribal councils in Alaska, Yukon and the Northwest Territories will provide a further impetus to northern research beyond that already in place for 40 years, based largely upon renewable and non-renewable natural resources. The founding principles of the Institute will serve it well in the context of northern scholarship in the 1990s and 2000s, drawing support from recent Canadian and American evaluations of arctic science policy.Key words: Arctic, Arctic Institute of North America, binationalism, multidisciplinary, northern science, northern scholarship Durant ses 40 ans de publication trimestrielle ininterrompue, le journal Arctic a retracé l'évolution intellectuelle des études canadiennes et américaines sur le Nord. Ces études étaient motivées par des préoccupations qui se rattachaient à divers thèmes du Grand Nord comme le système politique, les ressources naturelles, l'activité militaire, le changement culturel, la question de la souveraineté et les sciences naturelles. Il est clair que l'avenir de la science du Grand Nord repose en très grande partie sur des systèmes d'information polaire intégrés et sur une sorte d'institut polaire centralement reconnu qui favoriserait un bi-nationalisme, une approche multidisciplinaire et des publications recouvrant toute la zone circumpolaire. Les conseils des tribus auto-gouvernées, auto-suffisantes et propriétaires des terres en Alaska, au Yukon et ...